EARLY ISLAMIC BANKING PRACTICES AND CURRENT DEVELOPMENT: A SURVEY OF LEGAL HISTORY AND SERVICE INNOVATION - JM Muslimin (NISBAH: Jurnal Perbanka Syariah, 2019)
This study aims to determine the practice of Islamic banking in the early days of Islam and its development to date from the legal aspects and service innovations used by banks. This research method uses qualitative research with data collection techniques using literature studies relating to Islamic banking practices from the beginning of Islam to the present. The results of this study indicate that not all Islamic banking products and services are unanimously accepted in all Islamic financial institutions, such as bay al-‘inah and bay al-dayn which are conducted in Malaysia but not in the Middle East. This is because it refers to differences in views about the halality of the two products.